Rainforest animals - Alderton, David (Loughborough Ladybird, 1995)
Part of a series, this book provides information about the variety of animals that live in the jungle rainforests around the world. It explains where they are found, which mammals, insects, reptiles, birds, fish and plants live there, and how humans have affected the environment.